Mind the gap!: Stylized dynamic facts and structural models - Fabio Canova; Filippo Ferroni (Federal Reserve Bank of Chicago, 2020)
We study what happens to identified shocks and to dynamic responses when the data generating process features q disturbances but q1 < q variables are used in an empirical model. Identified shocks are linear combinations of current and past values of all structural disturbances and do not necessarily combine disturbances of the same type. Theory-based restrictions may be insufficient to obtain structural dynamics. We revisit the evidence regarding the transmission of house price and of uncertainty shocks. We provide suggestions on how to validate the dynamics of larger scale DSGEs with smaller scale VARs.
Keywords: C32; E27; E32; 330; Deformation; state variables; dynamic responses; structural models; house priceshocks; uncertainty shocks